Early Childhood Conditions and Adolescent Mental Health - Bilge Erten; Pinar Keskin; Rodrigo Pinto; Huihua Xie; Lianming Zhu (Institute of Labor Economics (IZA), 2023)
We investigate how early life circumstances induced by trade liberalization affect adolescent mental health in China, exploiting variation in tariff uncertainty faced by prefecture economies pre-2001. Our model differs from the classic difference-indifferences design in that it considers a moderator variable determining the intensity with which the treatment affects the outcomes. Our findings show that children born in prefectures more exposed to an exogenous change in international trade policy experienced a significant decline in the incidence of severe depression during adolescence. We find that the estimated relationships are robust to controls for initial prefecture attributes and other policy changes. Improvements in parental income, early childhood investments, and care provision in formal early childhood education programs are likely operative channels of impact.
Keywords: F16; I15; J13; C21; 330; China; trade reform; mental health; early life investments